Method and system for purifying helium by membrane separation coupled with two-stage dehydrogenation
Through the membrane separation and coupling two-stage dehydrogenation process, polymer film, catalytic dehydrogenation and alloy adsorption technology are used to solve the problem of low hydrogen removal efficiency in existing helium purification technologies, and the preparation and efficient utilization of high-purity helium are achieved.
Patent Information
- Application Number
- CN202111128998.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-09-26
AI Technical Summary
The existing helium purification technology is difficult to efficiently remove hydrogen from the gas, resulting in low ultra-pure helium extraction efficiency, complex process and high energy consumption.
The two-stage dehydrogenation process of membrane separation and coupling is adopted, firstly, most of the impurity gas is removed by separation of the polymer film, and then the helium is further purified by catalytic dehydrogenation and alloy adsorption.
The preparation of high-purity helium (level 5N or above) has been achieved, which reduces the energy consumption and equipment requirements of the helium extraction process. The process is simple and economical, continuous and stable, and solves the problem of ultra-pure helium preparation.
Smart Images

Figure CN115869739B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of helium purification, and in particular to a method and system for purifying helium by membrane separation coupled with two-stage dehydrogenation. Background Art
[0002] Helium is widely used in aerospace, refrigeration, medical, optical fiber, leak detection, deep-sea diving, high-precision welding production and other fields due to its low density, low boiling point and inert properties. Some groundwater and some natural gas contain a small amount of helium. In particular, after LNG products are produced from natural gas, the helium concentration in the tail gas (BOG) increases to 1-10%. At present, the widely used separation technologies include cryogenic technology, membrane technology, adsorption technology, and distillation technology. The combination of these technologies can effectively enrich, separate and purify helium. However, the extremely low boiling point and small size of hydrogen in the gas is difficult to be efficiently separated from helium. With the increase of the target helium concentration, the complexity and energy consumption of the process or equipment increase significantly, especially the process with cryogenic technology as the core. Efficient dehydrogenation has become a key step in the preparation of ultra-pure helium. Most helium refinements use catalytic dehydrogenation technology. The principle of dehydrogenation is to convert hydrogen into water more gently under the action of a catalyst, but its catalytic oxidation efficiency, reaction conditions and reaction energy consumption are mainly restricted by the performance of the catalyst, and the removal effect of trace hydrogen is limited. How to economically and efficiently extract ultrapure helium has not yet been effectively solved. Summary of the invention
[0003] In order to solve the technical problems existing in the prior art, the present invention provides a method and system for purifying helium by membrane separation coupled with two-stage dehydrogenation.
[0004] The first aspect of the present invention provides a method for purifying helium by membrane separation coupled with two-stage dehydrogenation, the method comprising: subjecting feed gas to polymer membrane separation, catalytic dehydrogenation and alloy adsorption in sequence to obtain ultrapure ultrapure helium.
[0005] The second aspect of the present invention provides a system for purifying helium by membrane separation coupled with two-stage dehydrogenation, the system comprising a polymer membrane separation unit, a catalytic dehydrogenation unit and an alloy adsorption unit connected in sequence;
[0006] Preferably, the catalytic dehydrogenation unit comprises a catalytic oxidation device and a pressure swing adsorption device.
[0007] Compared with the prior art, the present invention has the following beneficial effects:
[0008] The present invention combines polymer membrane separation (preferably multi-stage membrane separation), catalytic dehydrogenation and alloy adsorption processes specifically and effectively, and uses natural gas, shale gas, multi-stage flash gas, etc. as raw gas to prepare high-purity helium (5N level or above), and the conditions of each process are stable and controllable. Compared with the cryogenic process, it has the characteristics of compact equipment and low energy consumption. Compared with conventional catalytic dehydrogenation, the catalytic dehydrogenation technology used in this process can be carried out at a lower temperature, and the operating conditions are more stable and controllable. After the present invention removes most of the impurity gases such as CO2, N2, and methane through polymer membrane separation, the catalytic dehydrogenation and alloy adsorption dehydrogenation processes can raise helium to above 5N level at a relatively mild temperature, reducing the energy consumption and equipment requirements of the helium extraction process. Combining the advantages of each process technology, the helium preparation process is simple, economical, continuous and stable, solving the problem of ultra-pure helium preparation, and can realize efficient utilization of helium resources including natural gas, oilfield associated gas, chemical industry and other waste gases. The prepared helium is of very high value and has a very broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 This is the infrared spectrum of the polyimide random copolymer prepared in Preparation Example 1. DETAILED DESCRIPTION
[0010] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0011] The first aspect of the present invention provides a method for purifying helium by membrane separation coupled with two-stage dehydrogenation, the method comprising: subjecting feed gas to polymer membrane separation, catalytic dehydrogenation and alloy adsorption in sequence to obtain ultrapure ultrapure helium.
[0012] According to some embodiments of the present invention, the feed gas may be selected from at least one of natural gas, shale gas, helium-rich hydrogen-containing gas, and liquefied natural gas flash steam (BOG).
[0013] In the present invention, the feed gas is subjected to polymer membrane separation, catalytic dehydrogenation and alloy adsorption in sequence. First, the feed gas is subjected to polymer membrane separation to preliminarily enrich the hydrogen, which can improve the processing efficiency of catalytic dehydrogenation and reduce the cost of catalytic dehydrogenation (such as by reducing the intake volume, reducing the volume of the device, etc.), and then combined with alloy adsorption, it can complement the catalytic dehydrogenation unit, so that the hydrogen in the system is further removed to obtain ultra-pure helium.
[0014] According to some embodiments of the present invention, the polymer membrane used in the polymer membrane separation is selected from at least one of a hollow fiber membrane, a flat membrane and a tubular membrane; more preferably, it is a hollow fiber membrane.
[0015] In the present invention, there is no particular limitation on the polymer membrane used for the polymer membrane separation, as long as it can meet the requirements of the present invention, it can be obtained commercially, or it can be prepared by referring to conventional methods in the art such as phase separation, solution phase separation, melt stretching, interfacial polymerization, coating polymerization, in situ polymerization, etc.
[0016] According to some embodiments of the present invention, the material of the polymer film may be selected from at least one of polyimide, polybenzimidazole and polysulfone, and is more preferably polyimide.
[0017] According to some embodiments of the present invention, the polymer membrane separation adopts a one-stage or multi-stage (two to five-stage) separation method. Among them, the two-stage membrane separation refers to the polymer membrane separation in which the gas on the permeate side is pressurized and then used as the inlet of the membrane again. Tertiary membrane separation, four-stage membrane separation and five-stage membrane separation have similar meanings. Among them, the process of polymer membrane separation can be one to five stages. Preferably, multi-stage membrane separation is separation through multiple membranes or membrane components. Among them, the first-stage membrane separation, the second-stage membrane separation, the third-stage membrane separation, the fourth-stage membrane separation, and the fifth-stage membrane separation are respectively carried out in the first-stage membrane separation unit, the second-stage membrane separation unit, the third-stage membrane separation unit, the third-stage membrane separation unit, and the fourth-stage membrane separation unit.
[0018] According to some embodiments of the present invention, the conditions for polymer membrane separation may include: before polymer membrane separation, controlling the pressure of the feed gas (polymer membrane separation pressure) to 0.01-50 MPa and the gas temperature to 20-100°C.
[0019] In the present invention, according to a preferred embodiment, the feed gas enters the polymer membrane separation stage, wherein the permeate gas of the first membrane (first membrane separation unit) is pressurized to 0.01-10 MPa by a compressor and enters the next membrane after heat exchange by a heat exchanger, and the retentate gas enters the inlet of the first membrane or is discharged for collection;
[0020] The permeate gas of the secondary membrane (second-stage membrane separation unit) is pressurized to 0.1-10MPa by a 1^^ compressor and then enters the tertiary membrane or directly enters the next unit after heat exchange. The residual gas of the secondary membrane enters the inlet of the secondary membrane or the primary membrane or is discharged for collection;
[0021] The permeate gas of the tertiary membrane (third-stage membrane separation unit) is pressurized to 0.1-5MPa by a 1^^^ compressor and enters the quaternary membrane or directly enters the next unit after heat exchange by a heat exchanger. The residual gas of the tertiary membrane enters the inlet of the first or second membrane or is discharged for collection;
[0022] The permeate gas of the quaternary membrane (fourth-stage membrane separation unit) is pressurized to 0.01-5MPa by a 1^^^^ compressor and enters the fifth-stage membrane or directly enters the next unit after heat exchange by a heat exchanger. The residual gas of the quaternary membrane enters the inlet of the first, second or third-stage membrane or is discharged for collection;
[0023] The permeate gas of the five-stage membrane (fifth-stage membrane separation unit) is pressurized to 0.1-5MPa by a 1^^^^^ compressor, and then enters the four-stage membrane or directly enters the next unit after heat exchange through a heat exchanger. The residual gas of the three-stage membrane enters the inlet of the first, second, third or fourth membrane or is discharged for collection.
[0024] Among them, "1^^" stands for "one-stage membrane and two-stage membrane", "1" is a stage and "^^" is a level; "1^^^", "1^^^^" and "1^^^^^" have similar meanings.
[0025] According to some embodiments of the present invention, the polymer membrane used in the polymer membrane separation is a polyimide-based hollow fiber membrane.
[0026] Preferably, the polyimide-based hollow fiber membrane comprises a support layer and a dense layer attached to the outer surface of the support layer, the thickness of the dense layer is less than 1000 nm, and the porosity of the hollow fiber membrane is 40-80%.
[0027] Preferably, the thickness of the dense layer is 100-500 nm, and the porosity of the hollow fiber membrane is 50-70%.
[0028] Preferably, the hollow fiber membrane is made of polyimide random copolymer.
[0029] According to some embodiments of the present invention, the polyimide random copolymer has a structure shown in formula (I):
[0030]
[0031] In formula (I), m and n are each independently an integer of 10-2000;
[0032] X has a structure represented by any one of formula (X1) to formula (X3);
[0033]
[0034] In formula (X1) to formula (X3), R 1 , R 2 , R 3 , R 4 , R 5 and R 6 Each is independently H, C1-C4 alkyl, C6-C10 aryl, amino, hydroxyl or carboxyl;
[0035] Y has a structure represented by any one of formula (Y1) to formula (Y5);
[0036]
[0037] In formula (Y1) to formula (Y5), R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , R 15 and R 16 Each is independently H, C1-C4 alkyl, C6-C10 aryl, amino, hydroxyl or carboxyl;
[0038] Z and Z' each independently have a structure represented by formula (Z1) or formula (Z2);
[0039]
[0040] In formula (Z2), Ra and Rb are each independently H, C1-C4 alkyl or C1-C4 halogenated alkyl.
[0041] Preferably, m and n are each independently an integer of 50-1000.
[0042] Preferably, 0.9≥n / (m+n)≥0.3, preferably, 0.7≥n / (m+n)≥0.5.
[0043] In the present invention, X has one of the following structures:
[0044]
[0045] In the present invention, Y has one of the following structures,
[0046]
[0047] In the present invention, Z and Z' both have the structure shown by Z1 or Z3,
[0048]
[0049] Preferably, X is Xa, Y is Ya, and Z and Z' are both Z1;
[0050] Alternatively, X is Xa, Y is Yb, and Z and Z' are both Z1;
[0051] Or, X is Xa, Y is Yd, and Z and Z' are both Z1;
[0052] Or, X is Xb, Y is Ya, and Z and Z' are both Z1;
[0053] Or, X is Xb, Y is Yb, and Z and Z' are both Z1;
[0054] Or, X is Xb, Y is Yd, and Z and Z' are both Z1;
[0055] Or, X is Xc, Y is Ya, and Z and Z' are both Z1;
[0056] Alternatively, X is Xc, Y is Yb, and Z and Z' are both Z1;
[0057] Or, X is Xc, Y is Yc, and Z and Z' are both Z1;
[0058] Alternatively, X is Xc, Y is Y4, and Z and Z' are both Z1;
[0059] Or, X is Xc, Y is Yd, and Z and Z' are both Z1;
[0060] Or, X is Xb, Y is Ya, and Z and Z' are both Z3;
[0061] Or, X is Xb, Y is Yb, and Z and Z' are both Z3;
[0062] Or, X is Xb, Y is Yd, and Z and Z' are both Z3;
[0063] Or, X is Xc, Y is Ya, and Z and Z' are both Z3;
[0064] Or, X is Xc, Y is Yb, and Z and Z' are both Z3;
[0065] Alternatively, X is Xc, Y is Yd, and Z and Z' are both Z3.
[0066] Although according to a preferred embodiment of the present invention, X, Y, and Z have a specific structure, the present invention does not exclude the situation that "X is taken from two or three different structures, Y is taken from two, three, four or five different structures, and Z is taken from two different structures".
[0067] In the present invention, based on firstly carrying out polycondensation reaction of dianhydride monomer (dianhydride shown in formula (II) and dianhydride shown in formula (III)) and diamine monomer to obtain polyamic acid, then imidization (intramolecular dehydration) is carried out to polyamic acid, dianhydride monomer and diamine monomer can be carried out polycondensation reaction to obtain polyamic acid by one-pot method, or dianhydride monomer (i.e. dianhydride shown in formula (II) and dianhydride shown in formula (III)) can be mixed uniformly before carrying out polycondensation reaction with diamine monomer. However, in order to better control the reaction, it is preferred to react in the latter mode. Therefore, the present invention also provides a method for preparing polyimide random copolymer, and the method comprises the following steps:
[0068] (S1) in the presence of a first solvent, mixing a mixture of a dianhydride monomer represented by formula (II) and a dianhydride monomer represented by formula (III) with a diamine monomer to carry out a polycondensation reaction to obtain a material containing polyamic acid,
[0069]
[0070] (S2) imidizing the material containing polyamic acid obtained in step (S1) to cause intramolecular dehydration of the polyamic acid to obtain a polyimide random copolymer;
[0071] In formula (II) and formula (III), X and Y have the same meanings as described above.
[0072] The diamine monomer is selected from at least one of the compounds having a structure such as H2N-Zp-NH2, wherein Zp has a structure as shown in formula (Z1) or (Z2),
[0073]
[0074] In formula (Z2), Ra and Rb are each independently H, C1-C4 alkyl or C1-C4 halogenated alkyl.
[0075] Preferably, X is Xa, Y is Ya, and Zp is Z1;
[0076] Alternatively, X is Xa, Y is Yb, and Zp is Z1;
[0077] Or, X is Xa, Y is Yd, and Zp is Z1;
[0078] Or, X is Xb, Y is Ya, and Zp is Z1;
[0079] Or, X is Xb, Y is Yb, and Zp is Z1;
[0080] Or, X is Xb, Y is Yd, and Zp is Z1;
[0081] Or, X is Xc, Y is Ya, and Zp is Z1;
[0082] Or, X is Xc, Y is Yb, and Zp is Z1;
[0083] Or, X is Xc, Y is Yc, and Zp is Z1;
[0084] Or, X is Xc, Y is Y4, and Zp is Z1;
[0085] Or, X is Xc, Y is Yd, and Zp is Z1;
[0086] Or, X is Xb, Y is Ya, and Zp is Z3;
[0087] Or, X is Xb, Y is Yb, and Zp is Z3;
[0088] Or, X is Xb, Y is Yd, and Zp is Z3;
[0089] Or, X is Xc, Y is Ya, and Zp is Z3;
[0090] Or, X is Xc, Y is Yb, and Zp is Z3;
[0091] Alternatively, X is Xc, Y is Yd, and Zp is Z3.
[0092] In the present invention, the molar amounts of the dianhydride monomer represented by formula (II) and the dianhydride monomer represented by formula (III) are defined as M and N, respectively, and the ratio of M to N is (10-2000):(10-2000), more preferably 1:(0.5-15), and further preferably 1:(1-9).
[0093] In the present invention, M and N satisfy 0.9≥N / (M+N)≥0.3, preferably, 0.7≥N / (M+N)≥0.5.
[0094] In the present invention, the molar ratio of the total amount of the dianhydride monomer represented by formula (II) and the dianhydride monomer represented by formula (III) to the diamine monomer is 1:(0.6-1.5), preferably 1:(0.8-1.2).
[0095] In the present invention, in step (S1), the polycondensation reaction conditions may include: reaction temperature of -20°C to 60°C, preferably -10°C to 40°C; reaction time of 5-30h, preferably 8-24h.
[0096] In the present invention, the polycondensation reaction is carried out under an inert atmosphere, which is preferably provided by nitrogen.
[0097] In the present invention, the first solvent can be selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone (NMP), preferably selected from N-methylpyrrolidone and / or N,N-dimethylformamide.
[0098] In the present invention, the usage of the first solvent is 1000-3000 mL relative to 1 mmol of the diamine monomer.
[0099] In the present invention, the dianhydride monomer represented by formula (II) and the dianhydride monomer represented by formula (III) can be mixed to obtain a mixture by the following methods: mechanical stirring, shaking or ultrasound. The mechanical stirring conditions may include: 20-40°C, 2000-15000rpm, 2-12h; the ultrasound conditions may include: 20-40°C, 0.5-2.0h; the shaking conditions may include: 20-40°C, 260-800rpm, 12-36h.
[0100] In the present invention, the imidization treatment is carried out by adding a dehydrating agent and a catalyst to the amic acid-containing material obtained in step (S1), and reacting at 170-200° C. for 12-24 hours.
[0101] In the present invention, the dehydrating agent is selected from at least one of dichlorobenzene, toluene, acetic anhydride and xylene.
[0102] In the present invention, the catalyst is selected from pyridine and / or diquinoline.
[0103] In the present invention, the amount of the dehydrating agent used may be 2-15 mol, preferably 3-8 mol, relative to 1 mol of the diamine monomer.
[0104] In the present invention, the amount of the catalyst used may be 2-15 mol, preferably 3-8 mol, relative to 1 mol of the diamine monomer.
[0105] In the present invention, the method further comprises: before obtaining the polyimide copolymer, the material after the imidization treatment in step (S2) is diluted and contacted with a precipitant to obtain the polyimide copolymer. Wherein, the precipitant can be a poor solvent for polyimide, selected from at least one of ethanol, acetone and water, and more preferably selected from at least two of ethanol, acetone and water. Equivalent to 1 mol of diamine monomer, the total amount of the precipitant can be 10-50L. Wherein, the solvent for dilution can be N-methylpyrrolidone. Preferably, relative to 1 mol of diamine monomer, the amount of the solvent for dilution can be 5-8L.
[0106] In the present invention, there is no particular limitation on the manner in which the imidization-treated material in step (S2) is contacted with the precipitant, as long as the requirements of the present invention are met. For example, the following manner may be used: the imidization-treated material in step (S2) (after dilution) is added to the precipitant to precipitate the polyimide, and then the precipitated polyimide is eluted with the precipitant (the elution may be 3-5 times), and finally filtered and dried (70-150° C., 24-48 hours) to obtain a polyimide random copolymer.
[0107] In the present invention, the polyimide-based hollow fiber membrane is prepared according to a method comprising the following steps:
[0108] (1) preparing a casting solution containing a polyimide, a diluent and an additive, wherein the diluent contains a good solvent for the polyimide, a poor solvent for the first polyimide and a poor solvent for the second polyimide, wherein the boiling point B1 of the poor solvent for the first polyimide is higher than the boiling point B2 of the poor solvent for the second polyimide;
[0109] (2) extruding the inner core liquid and the casting liquid at a temperature T, and then curing to obtain a hollow fiber membrane precursor, wherein B2≤T<B1;
[0110] (3) The hollow fiber membrane precursor is rolled up and extracted to obtain the polyimide-based hollow fiber membrane.
[0111] In the present invention, in step (1), based on the total weight of the casting solution, the content of the polyimide is 20-40wt%, the content of the diluent is 50-75wt%, and the content of the additive is 0.5-10wt%.
[0112] Preferably, based on the total weight of the casting solution, the content of the polyimide is 25-35wt%, the content of the diluent is 60-70wt%, and the content of the additive is 1-5wt%.
[0113] In the present invention, in order to facilitate the formation of the dense layer of the hollow fiber membrane, the boiling point B1 of the first polyimide poor solvent is 5-200° C. higher than the boiling point B2 of the second polyimide poor solvent, preferably 10-20° C. higher. Wherein, the boiling point refers to the normal pressure boiling point unless otherwise specified.
[0114] In the present invention, the poor solvent for the first polyimide is at least one selected from the group consisting of a C2-C4 saturated monohydric alcohol, γ-butyrolactone and water.
[0115] In the present invention, the poor solvent for the second polyimide is at least one selected from C3-C5 alkanes, tetrahydrofuran, acetone and chloroform.
[0116] In the present invention, the good solvent for the polyimide is at least one selected from N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylacetamide.
[0117] In the present invention, in order to obtain better effects, the present invention has certain requirements on the usage ratio of the good solvent of the polyimide, the poor solvent of the first polyimide and the second polyimide. Preferably, the weight ratio of the good solvent of the polyimide, the poor solvent of the first polyimide and the poor solvent of the second polyimide is 1:(0.1-0.5):(0.1-0.5), preferably 1:(0.15-0.3):(0.15-0.3).
[0118] In the present invention, the additive may be a lithium salt, preferably selected from lithium nitrate and / or lithium chloride.
[0119] In the present invention, in step (1), the casting solution is prepared according to a method comprising the following steps: stirring polyimide, a diluent and an additive at 20-50°C and 100-1200 r / min for 12-48 hours, and then removing impurities by vacuum degassing and filtering (20-50°C).
[0120] In the present invention, the vacuum degassing conditions include: pressure of -0.1MPa to -0.095MPa, temperature of 20-30°C, rotation speed of 10-50r / min, and time of 12-24h.
[0121] In the present invention, in step (2), the inner core liquid includes solvent A and solvent B, wherein the solvent A is selected from at least one of N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylacetamide, and the solvent B is selected from at least one of a saturated monohydric alcohol of C1-C4, γ-butyrolactone and water.
[0122] In the present invention, the solvent A accounts for 50-99wt%, preferably 60-95wt%, of the total weight of the inner core liquid.
[0123] According to some embodiments of the present invention, the extrusion is carried out in a spinneret, wherein the extrusion temperature (temperature of the spinneret) is 40-75°C, preferably 60-70°C.
[0124] In the present invention, during the extrusion process, the flow rate of the casting solution is 6-30 mL / min.
[0125] According to some embodiments of the present invention, during the extrusion process, the flow rate of the core liquid is 2-10 mL / min.
[0126] In the present invention, before solidification, the hollow fibers obtained by extrusion are passed through an air gap to promote the formation of a dense layer and better control the thickness of the dense layer.
[0127] In the present invention, the height of the air gap is 5-30 cm.
[0128] In the present invention, the air gap is heated by an annular sleeve, and the temperature is preferably controlled to be 70-150°C.
[0129] In the present invention, the solidification is carried out in a coagulation bath. Preferably, the bath liquid used in the coagulation bath is solvent C and / or water, and the temperature of the coagulation bath is 40-70°C.
[0130] In the present invention, the solvent C is selected from at least one of a C1-C4 saturated monohydric alcohol, γ-butyrolactone and water.
[0131] In the present invention, in step (3), the winding rate is 0.5-2 m / s.
[0132] In the present invention, the purpose of the extraction is to remove the diluent and additives in the hollow fiber membrane precursor.
[0133] In the present invention, the extractant used for extraction is selected from at least one of water, C1-C4 saturated monohydric alcohol and C5-C7 alkane. There is no particular limitation on the amount of the extractant, as long as it can meet the requirements of the present invention.
[0134] In the present invention, the extraction conditions include: a temperature of 20-35° C. and a time of 3-48 hours. The extraction time refers to the time for the membrane fibers (hollow fiber membrane precursors) to be immersed.
[0135] In the present invention, preferably, the extraction method is preferably: extracting in water, C1-C4 saturated monohydric alcohol and C5-C7 alkane in sequence for 2-5 times respectively.
[0136] In the present invention, the extraction further includes a drying step.
[0137] In the present invention, the drying conditions include: temperature of 20-35° C. and time of 2-15 h.
[0138] According to some embodiments of the present invention, the catalytic dehydrogenation separation includes catalytic oxidation and adsorption, and the catalyst used in the catalytic oxidation is a precious metal catalyst selected from at least one of Pt, Pd, Rh, Ru and Au.
[0139] According to some embodiments of the present invention, the catalytic oxidation conditions include: a temperature of 30-150° C., preferably 50-120° C. wherein the space velocity of the gas concentrated by the polymer membrane is 1-10000 h -1 , preferably 10-1000h -1 .
[0140] According to some embodiments of the present invention, the adsorption method is pressure swing adsorption; the adsorbent used for adsorption is a molecular sieve. There is no particular limitation on the type of molecular sieve, as long as it can meet the requirements of the present invention. For example, the molecular sieve can be a zeolite molecular sieve.
[0141] According to some embodiments of the present invention, the adsorption (pressure swing adsorption) conditions may include: adsorption temperature of 5-50°C, preferably 10-30°C; adsorption pressure of 0.5-5MPa, preferably 2-4.5MPa.
[0142] According to some embodiments of the present invention, the alloy adsorption conditions may include: the alloy adsorption temperature is 10-80°C, preferably controlled to be 20-50°C.
[0143] According to some embodiments of the present invention, the adsorption material for alloy adsorption is a hydrogen storage alloy material, selected from at least one of rare earth alloys, titanium alloys, zirconium alloys, vanadium alloys and magnesium alloys.
[0144] In the present invention, the method further comprises: desorbing the adsorbed alloy material at 200-500° C. to obtain regenerated adsorbed material and desorbed gas, and returning (eg, reflux) the obtained desorbed gas to the catalytic oxidative dehydrogenation unit.
[0145] The second aspect of the present invention provides a system for purifying helium by membrane separation coupled with two-stage dehydrogenation, the system comprising a polymer membrane separation unit, a catalytic dehydrogenation unit and an alloy adsorption unit connected in sequence;
[0146] Preferably, the catalytic dehydrogenation unit comprises a catalytic oxidation device and a pressure swing adsorption device.
[0147] In the present invention, the meanings of abbreviations are:
[0148] PMDA: Pyromellitic anhydride
[0149] BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride
[0150] ODPA: 4,4'-diphenyl ether dianhydride
[0151] 6FDA: 4,4'-(Hexafluoroisopropylene) diphthalic anhydride
[0152] BTDA: 3,3',4,4'-Benzophenone tetracarboxylic dianhydride
[0153] TPDAn (a compound represented by formula (III), wherein Y is Yd): triptylenyl dianhydride (prepared by referring to “LUO SJ, WIEGAND JR, KAZANOWSKA B, et al. Finely Tuning the Free Volume Architecture in Iptycene-Containing Polyimides for Highly Selective and Fast Hydrogen Transport. Macromolecules 2016, 49, (9): 3395-3405”)
[0154] mPDA: meta-phenylenediamine
[0155] PPDA (structural formula: ): Pentiptycene diamine (prepared according to “LUO SJ, LIU Q, ZHANG BH, et al. Pentiptycene-based polyimides with hierarchically controlled molecular cavity architecture for efficient membrane gasseparation. J Membrane Sci 2015, 480: 20-30”)
[0156] The present invention will be described in detail below through examples.
[0157] In the following preparation examples, unless otherwise specified, all examples were commercially available; the hollow spinneret was purchased from Shanghai Zhanxin; the porosity of the hollow fiber membrane support layer was measured by mercury intrusion; and the thickness of the dense layer was measured by scanning electron microscopy.
[0158] In the following embodiments, the test method for the volume fraction of each gas is as follows: gas chromatography. In the embodiments, the primary membrane separation represents a polymer membrane separation, the secondary membrane separation represents the gas after the primary polymer separation is used as the inlet gas for polymer membrane separation again (using a fresh membrane assembly), and the tertiary membrane separation, the quaternary membrane separation and the quintuple membrane separation are similar.
[0159] In the following examples, the adsorbent used in the pressure swing adsorption unit is 13XAPG4×8 zeolite molecular sieve purchased from Shanghai Bojing Molecular Sieve Co., Ltd.
[0160] The following preparation examples are used to illustrate the preparation of polyimide random copolymers and polyimide flat films.
[0161] Preparation Example 1
[0162] (1) Under nitrogen protection, 200 mL of anhydrous N-methylpyrrolidone and m-phenylenediamine (10.81 g, 0.1 mmol) were added to a 1 L three-necked flask in sequence and stirred until the materials were completely dissolved; 4,4-diphenyl ether dianhydride (ODPA) (12.4138 g, 0.04 mmol) and 4,4'-(hexafluoroisopropylene) diphthalic anhydride (6FDA) (26.6544 g, 0.06 mmol) were mixed under mechanical stirring, and then added to the above system at 20° C. and polycondensed for 12 h to obtain a material containing polyimide acid;
[0163] (2) A mixture of acetic anhydride (36.7524 g, 0.36 mmol) and pyridine (28.4760 g, 0.36 mmol) was added to the polyimide acid material obtained in step (1), and intramolecular dehydration was performed at 180° C. for 18 h to obtain a material containing polyimide; then 600 mL of N-methylpyrrolidone (NMP) was added to the polyimide-containing material for dilution, and the diluted material was poured into a mixed solvent of water and ethanol (500 mL: 500 mL) under stirring to precipitate polyimide to obtain polyimide, and then the mixture was rinsed with a mixed solution of water and ethanol (1500 mL: 1500 mL) (3 times), and a polyimide random copolymer was obtained after suction filtration and drying. The polyimide random copolymer was subjected to infrared testing using a Fourier transform infrared spectrometer (Thermo Nicolet 380), and the infrared spectrum is shown in FIG. Figure 1 Infrared testing shows that the polyimide random copolymer has a structure shown in formula (I), wherein X is Xc, Y is Ya, and Z and Z' are both Z1. In addition, no raw materials are detected in the remaining liquid phase after the polyimide is precipitated, indicating that all raw materials participate in the reaction.
[0164] Figure 1 Medium, 1784cm -1 and 1730cm -1 The peaks at 1357 cm-1 are the symmetric stretching vibration peaks and asymmetric stretching vibration peaks of the two carbonyl groups on the five-membered imine ring in polyimide. -1 is the stretching vibration of CN in polyimide, 721 cm -1 is the deformation vibration peak of the imine ring, 1255cm -1 The stretching vibration of the ether bond in aromatic ether is 1144 cm -1 The stretching vibration peak of CF is shown in FIG. 4 , that is, the appearance of the above characteristic peak indicates the successful synthesis of the above polyimide copolymer.
[0165] Preparation Example 2
[0166] (1) Under nitrogen protection, 200 mL of anhydrous N-methylpyrrolidone and pentyl diamine (0.1 mmol) were added to a 1 L three-necked flask in sequence and stirred until the materials were completely dissolved; 4,4-diphenyl ether dianhydride (ODPA) (12.4138 g, 0.04 mmol) and tripteryl dianhydride (0.06 mmol) were mixed under mechanical stirring, and then added to the above system at 20° C. and polycondensed for 12 h to obtain a material containing polyimide acid;
[0167] (2) Add a mixture of acetic anhydride (36.7524 g, 0.36 mmol) and pyridine (28.4760 g, 0.36 mmol) to the polyimide acid material obtained in step (1), and perform intramolecular dehydration at 180°C for 18 hours to obtain a material containing polyimide; then add 600 mL of N-methylpyrrolidone (NMP) to the polyimide-containing material for dilution, and pour the diluted material into a mixed solvent of water and ethanol (500 mL: 500 mL) under stirring to precipitate polyimide to obtain polyimide, and then rinse with a mixed solution of water and ethanol (1500 mL: 1500 mL) (3 times), and obtain a polyimide random copolymer after suction filtration and drying. Infrared testing shows that the polyimide random copolymer has a structure shown in formula (I), wherein X is Xc, Y is Yd, and Z and Z' are both Z3. In addition, no raw materials were detected in the remaining liquid phase after the polyimide was precipitated, indicating that all the raw materials participated in the reaction.
[0168] The following preparation examples are used to illustrate the preparation of polyimide-based hollow fiber membranes.
[0169] Preparation Example 1
[0170] (1) Add 30 wt % of the random copolymer of polyimide obtained in the above-mentioned Preparation Example 1, 45 wt % of NMP, 10 wt % of ethanol (boiling point 78° C.), 10 wt % of THF (boiling point 68.28° C.) and 5 wt % of lithium nitrate into a kettle with a stirring device, heat to 50° C., and stir (speed 600 r / min) for 36 hours under nitrogen protection. After stopping stirring, degas at 25° C., -0.1 MPa, and speed 30 r / min for 24 hours, and then filter through a filter screen (pore size 100 mesh) at 50° C. to obtain a casting solution;
[0171] (2) using a metering pump to deliver the casting liquid and the inner core liquid (NMP: water = 95wt%: 5wt%) to the hollow spinneret, respectively, the inner core liquid and the casting liquid are extruded through the spinneret together to obtain a hollow fiber, the hollow fiber is passed through an air gap of 10 cm, and then placed in 50°C water for solidification to obtain a polyimide-based hollow fiber membrane precursor; wherein the spinneret temperature (extrusion temperature) is 75°C; the flow rates of the casting liquid and the inner core liquid entering the hollow spinneret are 6mL / min and 2mL / min, respectively;
[0172] (3) The polyimide hollow fiber membrane precursor obtained in step (2) is wound up by a winding machine, and then extracted twice in water, ethanol, and n-hexane in sequence, and the extraction time is 3 hours; then the extracted hollow fiber membrane is placed in a fume hood at room temperature and air-dried for 12 hours to obtain a polyimide-based hollow fiber membrane. The winding speed is 1 m / s.
[0173] The obtained hollow fiber membrane was characterized by mercury intrusion porosimetry, and the porosity was 59% and the thickness of the dense layer was 178 nm.
[0174] Preparation Example 2
[0175] (1) Add 30 wt % of the random copolymer of polyimide obtained in Preparation Example 2, 45 wt % of NMP, 10 wt % of ethanol (boiling point 78° C.), 10 wt % of THF (boiling point 68.28° C.) and 5 wt % of lithium nitrate into a kettle with a stirring device, heat to 50° C., and stir (speed 600 r / min) for 36 hours under nitrogen protection. After stopping stirring, degas at 25° C., -0.1 MPa, and speed 30 r / min for 24 hours, and then filter through a filter screen (pore size 100 mesh) at 50° C. to obtain a casting solution;
[0176] (2) using a metering pump to deliver the casting liquid and the inner core liquid (NMP: water = 95wt%: 5wt%) to the hollow spinneret, respectively, the inner core liquid and the casting liquid are extruded through the spinneret together to obtain a hollow fiber, the hollow fiber is passed through an air gap of 10 cm, and then placed in 50°C water for solidification to obtain a polyimide-based hollow fiber membrane precursor; wherein the spinneret temperature (extrusion temperature) is 75°C; the flow rates of the casting liquid and the inner core liquid entering the hollow spinneret are 6mL / min and 2mL / min, respectively;
[0177] (3) The polyimide hollow fiber membrane precursor obtained in step (2) is wound up by a winding machine, and then extracted twice in water, ethanol, and n-hexane in sequence, and the extraction time is 3 hours; then the extracted hollow fiber membrane is placed in a fume hood at room temperature and air-dried for 12 hours to obtain a polyimide-based hollow fiber membrane. The winding speed is 1 m / s.
[0178] The obtained hollow fiber membrane was characterized by mercury intrusion porosimetry, and the porosity was 68.5% and the thickness of the dense layer was 130 nm.
[0179] The following examples are used to illustrate the process of purifying helium using the method of the present invention.
[0180] Example 1
[0181] The natural gas extracted from a gas field is subjected to multi-stage flash evaporation to obtain raw gas, wherein the volume fraction of helium in the raw gas is 8.5%, and the composition of other gases includes: 35% by volume of methane, 37.3% by volume of nitrogen, 2.2% by volume of hydrogen, 7.5% by volume of carbon dioxide and 9.5% by volume of oxygen.
[0182] After the raw gas was heated to 25°C by a heat exchanger, the polyimide-based hollow fiber membrane module prepared in the above Preparation Example 1 was subjected to primary membrane separation and secondary membrane separation operations (the primary membrane inlet pressure was increased to 5MPa, and the secondary membrane pressure was increased to 3MPa). The gas concentrated by the polymer membrane was heated to 600h. -1 The air velocity is passed into the catalytic dehydrogenation unit, wherein Pt is used as a catalyst in the catalytic oxidation process, the catalytic temperature is 100°C, and the oxygen concentration is maintained at more than 8%. The gas from the outlet of the catalytic oxidation device is increased to 3MPa and the temperature is reduced to 20°C through heat exchange and passed into the pressure swing adsorption unit to remove water vapor. The gas after pressure swing adsorption enters the alloy adsorption separator (the alloy adsorption temperature is 20°C) for deep dehydrogenation to obtain ultra-pure helium products. The adsorbent is a magnesium-based hydrogen storage alloy (Mg2Ni, purchased from Xi'an Qiyue Biotechnology Co., Ltd.), and the desorbed gas is refluxed to the inlet of the catalytic dehydrogenation reactor, and the desorption temperature is 300°C. The volume fractions of the gas components after separation at each stage are shown in Table 1.
[0183] Table 1
[0184]
[0185]
[0186] Example 2
[0187] The flash gas from a liquefied natural gas station is used as the raw gas. In the raw gas, the volume fraction of helium is 15.73%, and the composition of other gases includes: 19.9% of methane, 57.7% of nitrogen, 5.62% of hydrogen, 1% of carbon dioxide and 0.05% of oxygen.
[0188] The raw gas was heated to 25°C by a heat exchanger and then passed through the polyimide hollow fiber membrane module prepared in the above-mentioned Preparation Example 1 for primary membrane separation and secondary membrane separation operations (the primary membrane inlet pressure was increased to 3MPa and the secondary membrane pressure was increased to 5MPa). The gas concentrated by the polymer membrane was heated for 800h. -1 The gas is passed into the catalytic dehydrogenation unit at a space velocity of 100 ° C. During the catalytic oxidation process, Ru is used as a catalyst, the catalytic temperature is 120 ° C, and the oxygen concentration is maintained at more than 8%. The gas from the outlet of the catalytic oxidation device is increased to 4.5 MPa and the temperature is reduced to 20 ° C by heat exchange. It is passed into the pressure swing adsorption unit to remove water vapor. The gas after pressure swing adsorption enters the alloy adsorption separator (the alloy adsorption temperature is 35 ° C) for deep dehydrogenation to obtain ultra-pure helium products. The adsorbent is a magnesium-based hydrogen storage alloy (Mg 1.92 Al 0.08 Ni, purchased from Xi'an Qiyue Biotechnology Co., Ltd.), the desorbed gas was refluxed to the inlet of the catalytic dehydrogenation reactor, and the desorption temperature was 400°C. The volume fractions of the gas components after separation at each stage are shown in Table 2.
[0189] Table 2
[0190]
[0191] Example 3
[0192] The natural gas extracted from a gas field is subjected to two-stage flash evaporation to obtain the raw gas, wherein the volume fraction of helium in the raw gas is 19.7%, and the composition of other gases includes: the volume fraction of methane is 15.9%, the volume fraction of nitrogen is 53.7%, the volume fraction of hydrogen is 0.05%, and the volume fraction of carbon dioxide is 10.65%;
[0193] The raw gas was heated to 30°C by a heat exchanger and then passed through the polyimide hollow fiber membrane module prepared in the above-mentioned Preparation Example 1 to perform primary, secondary, tertiary and quadruple membrane separation operations (the primary, secondary, tertiary and quadruple membrane inlet pressures were increased to 2MPa, 3MPa, 3MPa and 2.5MPa, respectively). The gas concentrated by the polymer membrane was heated to 560h. -1 The air velocity enters the catalytic dehydrogenation unit, wherein Pd is used as a catalyst in the catalytic oxidation process, the catalytic temperature is 63°C, and the oxygen concentration is maintained at more than 8%. The gas from the outlet of the catalytic oxidation device is pressurized to 2MPa and the temperature is reduced to 20°C through heat exchange and passed into the pressure swing adsorption unit to remove water vapor. The gas after pressure swing adsorption enters the alloy adsorption separator (the alloy adsorption temperature is 28°C) for deep dehydrogenation to obtain ultra-pure helium products. The adsorbent is LiBH4 hydrogen storage material (purchased from Xi'an Qiyue Biotechnology Co., Ltd.), and the desorbed gas is refluxed to the inlet of the catalytic dehydrogenation reactor, and the desorption temperature is 420°C. The volume fractions of the gas components after separation at each stage are shown in Table 3.
[0194] Table 3
[0195]
[0196] Example 4
[0197] The natural gas extracted from a gas field is subjected to multi-stage flash evaporation to obtain raw gas, wherein the volume fraction of helium in the raw gas is 10%, and the composition of other gases includes: methane with a volume fraction of 19.9%, nitrogen with a volume fraction of 55.5%, hydrogen with a volume fraction of 5.6%, carbon dioxide with a volume fraction of 6% and oxygen with a volume fraction of 3%;
[0198] After the raw gas was heated to 30°C by a heat exchanger, the polyimide-based hollow fiber membrane module prepared in the above Preparation Example 1 was subjected to primary membrane separation and secondary membrane separation operations (the primary membrane inlet pressure was increased to 4MPa, and the secondary membrane pressure was increased to 3MPa). The gas concentrated by the polymer membrane was heated to 450h. -1 The air velocity is passed into the catalytic dehydrogenation unit, wherein Pt is used as a catalyst in the catalytic oxidation process, the catalytic temperature is 80°C, and the oxygen concentration is maintained at more than 8%. The gas from the outlet of the catalytic oxidation device is pressurized to 3MPa and the temperature is reduced to 20°C through heat exchange and passed into the pressure swing adsorption unit to remove water vapor. The gas after pressure swing adsorption enters the alloy adsorption separator (the alloy adsorption temperature is 42°C) for deep dehydrogenation to obtain ultra-pure helium products. The adsorbent is a titanium-based hydrogen storage alloy (TiFe, purchased from Xi'an Qiyue Biotechnology Co., Ltd.), and the desorbed gas is refluxed to the inlet of the catalytic dehydrogenation reactor, and the desorption temperature is 350°C. The volume fractions of the gas components after separation at each stage are shown in Table 4.
[0199] Table 4
[0200]
[0201] Example 5
[0202] In the natural gas produced from a gas field, the volume fraction of helium is 2.6%, and the composition of other gases includes: 75% by volume of methane, 15.3% by volume of nitrogen, 2.1% by volume of hydrogen, 5.5% by volume of carbon dioxide and 1.5% by volume of oxygen;
[0203] The raw gas (the above-mentioned natural gas) was introduced into the polyimide-based hollow fiber membrane module prepared in the above-mentioned Preparation Example 1 to perform primary, secondary, tertiary, quaternary and quintuple membrane separation operations (the primary, secondary, tertiary, quaternary and quintuple membrane inlet pressures were increased to 2.5 MPa, 2.5 MPa, 3 MPa, 3 MPa and 4 MPa, respectively). The gas concentrated by the polymer membrane was heated for 200 h. -1The air velocity enters the catalytic dehydrogenation unit, wherein Au is used as a catalyst in the catalytic oxidation process, the catalytic temperature is 50°C, and the oxygen concentration is maintained at more than 8%. The gas from the outlet of the catalytic oxidation device is pressurized to 4.2MPa and the temperature is reduced to 20°C through heat exchange and passed into the pressure swing adsorption unit to remove water vapor. The gas after pressure swing adsorption enters the alloy adsorption separator (the alloy adsorption temperature is 50°C) for deep dehydrogenation to obtain ultra-pure helium products. The adsorbent uses a zirconium-based hydrogen storage alloy (ZrCr2-xMx system hexagonal Laves phase material, purchased from Xi'an Qiyue Biotechnology Co., Ltd.), and the desorbed gas is refluxed to the inlet of the catalytic dehydrogenation reactor, and the desorption temperature is 475°C. The volume fractions of the gas components after separation at each stage are shown in Table 5.
[0204] Table 5
[0205]
[0206] Example 6
[0207] The natural gas produced from a shale gas field is subjected to multi-stage flash evaporation to obtain raw gas. In the raw gas, the volume fraction of helium is 1.84%, and the composition of other gases includes: 94% by volume of methane, 3% by volume of nitrogen, 1.1% by volume of hydrogen, 0.01% by volume of carbon dioxide and 0.05% by volume of oxygen;
[0208] The raw gas was passed into the polyimide hollow fiber membrane module prepared in the above-mentioned Preparation Example 1 to perform primary, secondary and tertiary membrane separation operations (the primary, secondary and tertiary membrane inlet pressures were increased to 2MPa, 1.5MPa and 1.5MPa, respectively). The gas concentrated by the polymer membrane was heated for 1000h. -1 The air velocity enters the catalytic dehydrogenation unit, wherein Au is used as a catalyst in the catalytic oxidation process, the catalytic temperature is 99°C, and the oxygen concentration is maintained at more than 8%. The gas from the outlet of the catalytic oxidation device is cooled to 20°C by heat exchange and passed into the pressure swing adsorption unit to remove water vapor. The gas after pressure swing adsorption enters the alloy adsorption separator (the alloy adsorption temperature is 50°C) for deep dehydrogenation to obtain ultra-pure helium products. The adsorbent uses a zirconium-based hydrogen storage alloy (ZrMn2, purchased from Xi'an Qiyue Biotechnology Co., Ltd.), and the desorbed gas is refluxed to the inlet of the catalytic dehydrogenation reactor, and the desorption temperature is 320°C. The volume fractions of the gas components after separation at each stage are shown in Table 6.
[0209] Table 6
[0210]
[0211] Example 7
[0212] In the liquefied natural gas of a certain gas field, the volume fraction of helium is 3%, and the composition of other gases includes: 85% of methane, 4% of nitrogen, 5% of hydrogen, 3.2% of carbon dioxide and 0.8% of oxygen.
[0213] The raw gas (the above-mentioned natural gas) was introduced into the polyimide-based hollow fiber membrane module prepared in the above-mentioned Preparation Example 1 to perform primary, secondary and tertiary membrane separation operations (the primary, secondary and tertiary membrane inlet pressures were increased to 3MPa, 1MPa and 2MPa, respectively). The gas concentrated by the polymer membrane was heated for 400h. -1 The air velocity enters the catalytic dehydrogenation unit, wherein Pt is used as a catalyst in the catalytic oxidation process, the catalytic temperature is 120°C, and the oxygen concentration is maintained at more than 8%. The gas from the outlet of the catalytic oxidation device is cooled to 20°C by heat exchange and passed into the pressure swing adsorption unit to remove water vapor. The gas after pressure swing adsorption enters the alloy adsorption separator (the alloy adsorption temperature is 30°C) for deep dehydrogenation to obtain ultra-pure helium products. The adsorbent uses titanium hydrogen storage alloy (TiFe, purchased from Xi'an Qiyue Biotechnology Co., Ltd.), and the desorbed gas is refluxed to the inlet of the catalytic dehydrogenation reactor, and the desorption temperature is 240°C. The volume fractions of the gas components after separation at each stage are shown in Table 7.
[0214] Table 7
[0215]
[0216] Example 8
[0217] The natural gas extracted from a gas field is subjected to multi-stage flash evaporation to obtain raw gas. In the raw gas, the volume fraction of helium is 15%, and the composition of other gases includes: 20% by volume of methane, 46% by volume of nitrogen, 9% by volume of hydrogen, 5% by volume of carbon dioxide and 5% by volume of oxygen;
[0218] The raw gas was heated to 25°C by a heat exchanger and then passed through the tri-disc polyimide hollow fiber membrane module prepared in the above-mentioned Preparation Example 2 for primary membrane separation and secondary membrane separation (the primary membrane inlet pressure was increased to 5 MPa, and the secondary membrane pressure was increased to 5 MPa). The gas concentrated by the polymer membrane was heated to 460 h. -1) is passed into the catalytic dehydrogenation unit at a space velocity of 1.5 ℃, wherein Au is used as a catalyst in the catalytic oxidation process, the catalytic temperature is 86°C, and the oxygen concentration is maintained at more than 8%. The gas from the outlet of the catalytic oxidation device is cooled to 20°C by heat exchange and passed into the pressure swing adsorption unit to remove water vapor. The gas after pressure swing adsorption enters the alloy adsorption separator (the alloy adsorption temperature is 30°C) for deep dehydrogenation to obtain ultra-pure helium products. The adsorbent is a titanium-based hydrogen storage alloy (TiFe, purchased from Xi'an Qiyue Biotechnology Co., Ltd.), and the desorbed gas is refluxed to the inlet of the catalytic dehydrogenation reactor, and the desorption temperature is 400°C. The volume fractions of the gas components after separation at each stage are shown in Table 8.
[0219] Table 8
[0220]
[0221]
[0222] Example 9
[0223] In the natural gas produced from shale gas fields, the volume fraction of helium is 2%, and the composition of other gases includes: 88% by volume of methane, 2% by volume of nitrogen, 4% by volume of hydrogen, 3% by volume of carbon dioxide and 1% by volume of oxygen;
[0224] The raw gas (the above-mentioned natural gas) was heated to 30°C by a heat exchanger and then passed through a hollow fiber membrane module made of polybenzimidazole (Zhongke Energy Materials Technology (Dalian) Co., Ltd., PBI membrane) for primary, secondary, tertiary and quaternary membrane separation operations (the inlet pressure of the primary, secondary, tertiary and quaternary stages was increased to 5MPa, 5MPa, 5MPa and 5MPa respectively). The gas concentrated by the polymer membrane was heated for 60 hours. -1 The gas enters the catalytic dehydrogenation unit at a space velocity of 106°C. In the catalytic oxidation process, Pd is used as a catalyst, the catalytic temperature is 106°C, and the oxygen concentration is kept greater than 8%. The gas from the outlet of the catalytic oxidation device is cooled to 20°C by heat exchange and passed into the pressure swing adsorption unit to remove water vapor. The gas after pressure swing adsorption enters the alloy adsorption separator (the alloy adsorption temperature is 35°C) for deep dehydrogenation to obtain ultra-pure helium products. The adsorbent uses vanadium hydrogen storage alloy (VH2, purchased from Xi'an Qiyue Biotechnology Co., Ltd.), and the desorbed gas flows back to the inlet of the catalytic dehydrogenation reactor, and the desorption temperature is 400°C. The volume fractions of the gas components after separation at each stage are shown in Table 9.
[0225] Table 9
[0226]
[0227] It can be seen from the above results that the method of the present invention removes most of the impurity gases such as CO2, N2, and methane after concentration through a membrane separation unit (multi-stage membrane separation), greatly increases the content of helium and hydrogen in the gas, and effectively converts the hydrogen in the mixed gas into water vapor during the catalytic oxidation process, and the concentration of hydrogen can be reduced to 0.02% by volume. The water vapor generated by catalytic oxidation is removed during the pressure swing adsorption process, and finally the hydrogen and helium are completely separated through alloy adsorption to obtain a helium product concentration of 99.999%.
[0228] The polymer films of the preferred embodiments used in the present invention can achieve better results. For details, please refer to the contents recorded in (Application No. 202110864549.5).
[0229] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for purifying helium by membrane separation coupled with two-stage dehydrogenation, characterized in that: The method comprises: subjecting the raw gas to polymer membrane separation, catalytic dehydrogenation and alloy adsorption in sequence to obtain ultrapure helium; The polymer membrane used in the polymer membrane separation is a polyimide-based hollow fiber membrane, and the material of the hollow fiber membrane is a polyimide random copolymer; The polyimide random copolymer has a structure shown in formula (I): (I), In formula (I), m and n are each independently an integer of 10-2000, and 0.9≥n / (m+n)≥0.3; X has a structure represented by any one of formula (X1) to formula (X3); (X1)、 (X2)、 (X3), In formula (X1)-formula (X3), R 1 , R 2 , R 3 , R 4 , R 5 and R 6 Each is independently H, C1-C4 alkyl, C6-C10 aryl, amino, hydroxyl or carboxyl; Y has a structure represented by any one of formula (Y1) to formula (Y5); <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (Y1)<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (Y2)<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (Y3)<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (Y4)<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (Y5) In formula (Y1) to formula (Y5), R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , R 15 and R 16 Each is independently H, C1-C4 alkyl, C6-C10 aryl, amino, hydroxyl or carboxyl; Z and Z' each independently have a structure represented by formula (Z1) or formula (Z2); (Z1)、 (Z2), In formula (Z2), Ra and Rb are each independently H, C1-C4 alkyl or C1-C4 halogenated alkyl.
2. The method according to claim 1, wherein: The raw gas is selected from at least one of natural gas, shale gas, helium-rich hydrogen-containing gas and liquefied natural gas flash steam (BOG).
3. The method according to claim 1 or 2, wherein: The polymer membrane separation adopts a one-stage or multi-stage separation method; And / or, the conditions for polymer membrane separation include: before polymer membrane separation, the pressure of the feed gas is controlled to be 0.01-50 MPa, and the gas temperature is controlled to be 20-100°C.
4. The method according to claim 1, wherein: The polyimide-based hollow fiber membrane comprises a support layer and a dense layer attached to the outer surface of the support layer, the thickness of the dense layer is less than 1000nm, and the porosity of the hollow fiber membrane is 40-80%.
5. The method according to claim 4, wherein: The thickness of the dense layer is 100-500 nm, and the porosity of the hollow fiber membrane is 50-70%.
6. The method according to claim 1, wherein m and n are each independently an integer of 50-1000; And / or, 0.7≥n / (m+n)≥0.
5.
7. The method according to claim 1, wherein: The X has one of the following structures, 、 、 ; And / or, Y has one of the following structures, 、 、 、 、 ; and / or, Z and Z' both have the structure shown by Z1 or Z3, 、 。 8. The method according to claim 7, wherein: X is Xa, Y is Ya, and Z and Z' are both Z1; Alternatively, X is Xa, Y is Yb, and Z and Z' are both Z1; Or, X is Xa, Y is Yd, and Z and Z' are both Z1; Or, X is Xb, Y is Ya, and Z and Z' are both Z1; Or, X is Xb, Y is Yb, and Z and Z' are both Z1; Or, X is Xb, Y is Yd, and Z and Z' are both Z1; Or, X is Xc, Y is Ya, and Z and Z' are both Z1; Alternatively, X is Xc, Y is Yb, and Z and Z' are both Z1; Or, X is Xc, Y is Yc, and Z and Z' are both Z1; Alternatively, X is Xc, Y is Y4, and Z and Z' are both Z1; Or, X is Xc, Y is Yd, and Z and Z' are both Z1; Or, X is Xb, Y is Ya, and Z and Z' are both Z3; Or, X is Xb, Y is Yb, and Z and Z' are both Z3; Or, X is Xb, Y is Yd, and Z and Z' are both Z3; Or, X is Xc, Y is Ya, and Z and Z' are both Z3; Or, X is Xc, Y is Yb, and Z and Z' are both Z3; Alternatively, X is Xc, Y is Yd, and Z and Z' are both Z3.
9. The method according to claim 1, wherein: The polyimide-based hollow fiber membrane is prepared according to a method comprising the following steps: (1) preparing a casting solution containing a polyimide, a diluent and an additive, wherein the diluent contains a good solvent for the polyimide, a poor solvent for the first polyimide and a poor solvent for the second polyimide, wherein the boiling point B1 of the poor solvent for the first polyimide is higher than the boiling point B2 of the poor solvent for the second polyimide; (2) extruding the inner core liquid and the casting liquid at a temperature T, and then curing to obtain a hollow fiber membrane precursor, wherein B2≤T<B1; (3) The hollow fiber membrane precursor is rolled up and extracted to obtain the polyimide-based hollow fiber membrane.
10. The method according to claim 9, wherein: In step (1), based on the total weight of the casting solution, the content of the polyimide is 20-40wt%, the content of the diluent is 50-75wt%, and the content of the additive is 0.5-10wt%; and / or the boiling point B1 of the poor solvent for the first polyimide is 5-200° C. higher than the boiling point B2 of the poor solvent for the second polyimide; And / or, the good solvent of the polyimide is selected from at least one of N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylacetamide; and / or, the weight ratio of the good solvent for the polyimide, the poor solvent for the first polyimide and the poor solvent for the second polyimide is 1:(0.1-0.5):(0.1-0.5); And / or, the additive is a lithium salt.
11. The method according to claim 9, wherein: Based on the total weight of the casting solution, the content of the polyimide is 25-35wt%, the content of the diluent is 60-70wt%, and the content of the additive is 1-5wt%; and / or the boiling point B1 of the poor solvent for the first polyimide is 10-20° C. higher than the boiling point B2 of the poor solvent for the second polyimide; and / or, the weight ratio of the good solvent for the polyimide, the poor solvent for the first polyimide and the poor solvent for the second polyimide is 1:(0.15-0.3):(0.15-0.3); And / or, the additive is lithium nitrate and / or lithium chloride; and / or, the poor solvent of the first polyimide is selected from at least one of a C2-C4 saturated monohydric alcohol, γ-butyrolactone and water; And / or, the poor solvent for the second polyimide is at least one selected from C3-C5 alkanes, tetrahydrofuran, acetone and chloroform.
12. The method according to claim 9, wherein: The casting solution is prepared according to a method comprising the following steps: stirring polyimide, a diluent and an additive at 20-50° C. and 100-1200 r / min for 12-48 hours, and then removing impurities by vacuum degassing and filtering at 20-50° C.; And / or, the vacuum degassing conditions include: pressure of -0.1 MPa to -0.095 MPa, temperature of 20-30°C, rotation speed of 10-50 r / min, and time of 12-24 h.
13. The method according to claim 9, wherein: In step (2), the inner core liquid comprises solvent A and solvent B, wherein the solvent A is selected from at least one of N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylacetamide, and the solvent B is selected from at least one of C1-C4 saturated monohydric alcohol, γ-butyrolactone and water; and / or, the solvent A accounts for 50-99wt% of the total weight of the inner core liquid; And / or, the extrusion is carried out in a spinneret, wherein the extrusion temperature is 40-75°C; And / or, during the extrusion process, the flow rate of the casting solution is 6-30 mL / min; and / or, during the extrusion process, the flow rate of the inner core liquid is 2-10 mL / min; and / or, prior to solidification, passing the extruded hollow fibers through an air gap; And / or, the height of the air gap is 5-30 cm; And / or, the air gap is heated by an annular sleeve, and the temperature is controlled to be 70-150°C; and / or, the solidification is carried out in a coagulation bath; And / or, the bath liquid used in the coagulation bath is solvent C and / or water, and the temperature of the coagulation bath is 40-70°C; And / or, the solvent C is selected from at least one of a C1-C4 saturated monohydric alcohol, γ-butyrolactone and water.
14. The method according to claim 13, wherein: The solvent A accounts for 60-95% of the total weight of the inner core liquid; And / or, the extrusion temperature is 60-70°C.
15. The method according to claim 9, wherein: In step (3), the winding speed is 0.5-2 m / s; And / or, the extractant used for extraction is selected from at least one of water, C1-C4 saturated monohydric alcohol and C5-C7 alkane; And / or, the extraction conditions include: temperature of 20-35°C and time of 3-48h; And / or, the extraction further includes a drying step; And / or, the drying conditions include: temperature of 20-35° C. and time of 2-15 h.
16. The method according to claim 1 or 2, wherein: The catalytic dehydrogenation separation includes catalytic oxidation and adsorption, and the catalyst used in the catalytic oxidation is a precious metal catalyst selected from at least one of Pt, Pd, Rh, Ru and Au; And / or, the conditions for the catalytic oxidation include: a temperature of 30-150°C; And / or, the space velocity of the gas after polymer membrane concentration is 1-10000 h -1 ; And / or, the adsorption method is pressure swing adsorption; the adsorbent used for adsorption is molecular sieve; And / or, the adsorption conditions include: the adsorption temperature is 5-50° C.; the adsorption pressure is 0.5-5 MPa.
17. The method according to claim 16, wherein: The conditions for the catalytic oxidation include: a temperature of 50-120°C; And / or, the space velocity of the gas after polymer membrane concentration is 10-1000 h -1 ; And / or, the adsorbent used for adsorption is a zeolite molecular sieve; And / or, the adsorption conditions include: the adsorption temperature is 10-30° C.; the adsorption pressure is 2-4.5 MPa.
18. The method according to claim 1 or 2, wherein: The alloy adsorption conditions include: the alloy adsorption temperature is 10-80°C.
19. The method according to claim 18, wherein: The alloy adsorption conditions include: the alloy adsorption temperature is 20-50°C.
20. The method according to claim 1 or 2, wherein: The adsorption material for alloy adsorption is a hydrogen storage alloy material, which is selected from at least one of rare earth alloys, titanium alloys, zirconium alloys, vanadium alloys and magnesium alloys.
21. A system for purifying helium by membrane separation coupled with two-stage dehydrogenation, characterized in that: The system comprises a polymer membrane separation unit, a catalytic dehydrogenation unit and an alloy adsorption unit which are connected in sequence; The catalytic dehydrogenation unit includes a catalytic oxidation device and a pressure swing adsorption device; The polymer membrane used in the polymer membrane separation is a hollow fiber membrane, and the material of the hollow fiber membrane is a polyimide random copolymer; The polyimide random copolymer has a structure shown in formula (I): (I), In formula (I), m and n are each independently an integer of 10-2000, and 0.9≥n / (m+n)≥0.3; X has a structure represented by any one of formula (X1) to formula (X3); (X1)、 (X2)、 (X3), In formula (X1)-formula (X3), R 1 , R 2 , R 3 , R 4 , R 5 and R 6 Each is independently H, C1-C4 alkyl, C6-C10 aryl, amino, hydroxyl or carboxyl; Y has a structure represented by any one of formula (Y1) to formula (Y5); <h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (Y1)<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (Y2)<h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"> (Y3) (Y4) (Y5), In formula (Y1) to formula (Y5), R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , R 15 and R 16 Each is independently H, C1-C4 alkyl, C6-C10 aryl, amino, hydroxyl or carboxyl; Z and Z' each independently have a structure represented by formula (Z1) or formula (Z2); (Z1)、 (Z2), In formula (Z2), Ra and Rb are each independently H, C1-C4 alkyl or C1-C4 halogenated alkyl.
Citation Information
Patent Citations
Polyamide microporous membrane and preparation method thereof
CN102716680A
Preparation method of copolyimide hollow fiber gas separation membrane
CN103846022A
System and method for separating and purifying hydrogen and helium from BOG
CN111086974A
Polyimide for gas separation prepared based on diaminotriptycene and derivatives thereof and preparation method thereof
CN112574412A
Multi-technology integrated separation process for producing high-purity helium from liquefied tail gas of helium-rich natural gas
CN113144821A